Bronchial Injury After Atrial Fibrillation Ablation Using the Second-Generation Cryoballoon. (March 2018) - Bellmann, Barbara; Hübner, Ralf-Harto; Lin, Tina; Paland, Matthias; Steiner, Florian; Krause, Phillip; Tscholl, Verena; Nagel, Patrick; Roser, Mattias; Suttorp, Norbert; Landmesser, Ulf; Rillig, Andreas
Abstract : Supplemental Digital Content is available in the text.